2007
DOI: 10.1038/sj.jcbfm.9600594
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Depression in the Brainstem of the Adult Rat: Electrophysiological Parameters and Influences on Regional Brainstem Blood Flow

Abstract: Cortical spreading depression is a pathophysiological excitation wave that occurs during pathophysiological brain conditions such as ischemic brain infarction, migraine aura, and others. Judged from experiments in rodents, the brainstem is thought to be comparatively resistant to the generation of spreading depression. However, because spreading depression can be elicited in the brainstem of rat pups after superfusing the brainstem with solutions enhancing excitability, we reinvestigated spreading depression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 50 publications
2
29
1
2
Order By: Relevance
“…During SD, the regional blood flow in the brainstem is transiently increased. These data show that proper conditioning renders the brainstem susceptible to SD, and that SD at this brain location elicits changes in local circulation and systemic blood pressure (Richter et al 2008). …”
Section: Spreading Depression In Brainstemmentioning
confidence: 95%
“…During SD, the regional blood flow in the brainstem is transiently increased. These data show that proper conditioning renders the brainstem susceptible to SD, and that SD at this brain location elicits changes in local circulation and systemic blood pressure (Richter et al 2008). …”
Section: Spreading Depression In Brainstemmentioning
confidence: 95%
“…We recently found that spreading depression, which is detectable as a sudden propagating negative deflection in the extracellular DC potential and arises from a massive synchronized neuronal and glial depolarization as well as severe derangements of ionic distribution (for review see Somjen 2001), can also occur in rat brain stem, especially at infant stages (Funke et al 2009), a finding that extended earlier observations from in vivo recordings (Richter F et al , 2008(Richter F et al , 2010. Because the Mecp2 Ϫ/y hippocampus was found to be more susceptible to hypoxia and HSD, and HIF-1␣ expression was also increased in Mecp2 Ϫ/y brain stem (Fischer et al 2009), we now asked whether the generation of HSD episodes might be facilitated in brain stem as well.…”
mentioning
confidence: 81%
“…In all, 10 mmol/L TEA (Sigma, Seelze, Germany) and 10 mmol/L KCl were added to the acetate-ACSF (acetate-ACSF + TEA + KCl). This superfusate had successfully conditioned the adult rat brainstem for SD in previous experiments (Richter et al, 2008). The superfusion lasted for at least 1 hour and was only interrupted when 1 mol/L KCl (see above) was injected into the brainstem to test the elicitation of SD by KCl during a period of RD waves.…”
Section: Superfusion Of the Brainstem And Conditioning For Spreading mentioning
confidence: 99%
“…V) to a depth of 1,200 to 1,400 mm. To elicit SD by KCl, we injected B0.5 mL of 1 mol/L KCl as in our previous study (Richter et al, 2008) with a pressure of 100 kPa for 1 second using a microinjector (picoinjector PLI-100; Harvard Apparatus, Holliston, MA, USA). All electrodes were connected by Ag/AgCl wires to a custom built 4-channel-high impedance amplifier (Meyer, Munich, Germany).…”
Section: Recording Of Direct Current Potentialsmentioning
confidence: 99%
See 1 more Smart Citation